Image Recognition–Based Identification of Multifractal Features of Faults - Hu, Xiuquan; Liu, Hong; Tan, Xiucheng; Yi, Chi; Niu, Zhipeng; Li, Jianghan; Li, Jieyi (Frontiers in Earth Science, 2022)
Geologists have made many achievements in applying multifractal theory in geology, but there are some problems in the research process, such as large statistical workload and low efficiency. Thus, this work proposes an image-recognition-based method of calculating the multifractality of faults. First, grayscale processing and binarization of the fault distribution map is performed. The image is then gridded, and the grids are numbered. Next, a computer image recognition technique is used to count the number of faults in each grid, to replace manual counting. Finally, the fractal dimensions of the faults are calculated using the multifractal box-counting algorithm. This method is successfully applied to fracture study of the Maokou Formation in Southeast Sichuan. Compared with the conventional approach, the new method provides significantly improved work efficiency and accuracy. The results show that the faults in the study area exhibit good statistical self-similarity in the scale range, indicating fractal characteristics. The fractal dimensions of faults with different orientations and the planar distribution of the fractal dimension contours indicate the tectonic stages and stress magnitude in the study area. The results indicate that the tectonic setting of Southeast Sichuan was formed mainly during the Indosinian, Yanshanian, and Himalayan periods. From the Indosinian to Early Yanshanian, NE-trending faults with relatively large fractal dimensions developed under NW–SE compressional tectonic stress. From the Late Yanshanian to Early Himalayan, EW-trending faults were formed by relatively weak N–S compressional stress, and they have the lowest fractal dimensions. The NW-trending faults formed by intense NE–SW compressional tectonic stress in the Late Himalayan have the highest fractal dimensions. In order to promote oil and gas migration and ensure that faults do not destroy the caprock, oil and gas reservoirs need to be in a relatively gentle and relatively mild tectonic environment. Thus, the fractal dimensions of faults in favorable areas should be neither too high nor too low. The relationship between the fractal dimensions of faults and well test results in Southeast Sichuan indicates that the region along wells ls1–xia14–guan3 (with fractal dimensions of 1.49–1.57) in the study area is a relatively favorable region for oil and gas exploration.